Compliance after switching from CPAP to bilevel for patients with non-compliant OSA: big data analysis. (29th April 2019) - Benjafield, Adam V; Pepin, Jean-Louis D; Valentine, Kate; Cistulli, Peter A; Woehrle, Holger; Nunez, Carlos M; Armitstead, Jeff; Malhotra, Atul
Abstract : Introduction: For patients with obstructive sleep apnoea (OSA) who are initially non-compliant with continuous (automatic) positive airway pressure (CPAP/APAP) therapy, a bilevel PAP (Spont/VAuto) therapy transition pathway is available to improve therapy adherence. The aim of this retrospective study was to compare PAP therapy usage data of patients with non-compliant OSA (ncOSA) on CPAP/APAP who were switched to bilevel PAP. Methods: A PAP telemonitoring database was queried between 1 January 2015 and 31 July 2016 for eligible patients started on CPAP/APAP and non-CMS (United States Center for Medicare and Medicaid Services) compliant and switched to bilevel PAP within 90 days of starting CPAP/APAP therapy. PAP therapy data on all patients were compared before switch (CPAP/APAP) and after switch (VAuto/Spont). Results: Of the 1496 patients with ncOSA identified, 30.3% used CPAP, 62.3% APAP, and 7.4% both APAP and CPAP before switching to a bilevel mode. 47.8% patients switched to Spont mode and 52.2% to VAuto mode. PAP usage significantly improved by 0.9 h/day (p<0.001) and all other device metrics (residual apnoea–hypopnoea index and unintentional mask leak) also improved after the switch. No patients had achieved US CMS criteria for compliance before the switch, and 56.8% did after. Conclusion: This shows for the first time that there may be potential benefit from switching from CPAP/APAP to bilevel PAP for patients struggling with PAP adherence.